A review on electrospun magnetic nanomaterials: methods, properties and applications. Issue 29 (7th July 2021) - Jia, Yifan; Yang, Congyi; Chen, Xueyang; Xue, Wenqing; Hutchins-Crawford, Helena J.; Yu, Qianqian; Topham, Paul D.; Wang, Linge
Abstract : A comprehensive review summarising the methods, reagents, properties and applications of electrospun magnetic nanomaterials. Abstract : Magnetic materials display attractive properties for a wide range of applications. More recently, interest has turned to significantly enhancing their behaviour for advanced technologies, by exploiting the remarkable advantages that nanoscale materials offer over their bulk counterparts. Electrospinning is a high-throughput method that can continuously produce nanoscale fibres, providing a versatile way to prepare novel magnetic nanomaterials. This article reviews 20 years of magnetic nanomaterials fabricated via electrospinning and introduces their two primary production methods: electrospinning polymer-based magnetic fibres directly from solution and electrospinning fibrous templates for post-treatment. Continual advances in electrospinning have enabled access to a variety of morphologies, which has led to magnetic materials having desirable flexibility, anisotropy and high specific surface area. Post-treatment methods, such as surface deposition, carbonization and calcination, further improve or even create unique magnetic properties in the materials. This renders them useful in broad ranging applications, including electromagnetic interference shielding (EMS), magnetic separation, tissue engineering scaffolding, hyperthermia treatment, drug delivery, nanogenerators and data storage. The processing methods of electrospun magnetic nanofibres, their properties and related applications are discussed throughout this review. Key areas for future research have been highlighted with the aim of stimulating advances in the development of electrospun magnetic nanomaterials for a wide range of applications.